THE USE OF JOURNALING TO DEVELOP SELF-CONFIDENCE AND SELF-EXPRESSION SKILLS IN EARLY CHILDHOOD - Ulfah Dwi Lestari; Tri Sayekti; Kristiana Maryani (Department of Early Childhood Education, Universitas Bina Bangsa Getsempena, 2026)
Self-confidence is an important aspect of development that needs to be fostered from an early age. One activity that can support children’s self-expression and self-confidence is journaling, particularly through morning journaling activities. This study aims to describe the implementation of journaling in developing self-expression and self-confidence in early childhood. The study used a descriptive qualitative approach, involving four homeroom teachers from Group B as the main informants. Data were collected through participatory observation over eight days, semi-structured interviews, and documentation, and their validity was tested using triangulation of methods. The results of the study indicate that: (1) the morning journaling session was consistently conducted as an opening routine, giving children complete freedom to express themselves through drawings and writing; (2) teachers played an active role as facilitators and motivators through prompting questions, positive reinforcement, direct assistance, and storytelling opportunities; (3) supporting factors included punctual attendance, family support, and a warm welcome from teachers, while inhibiting factors included children’s tardiness, unstable emotional states, and limited time for guidance. Overall, the implementation of the morning journal indicates a positive contribution to the development of self-expression and self-confidence in early childhood, supported by teacher readiness, family involvement, and consistency in implementation.